Moonlight & Hokum The Kirov's "Homage to Diaghilev" reviewed - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of the Kirov's "Homage to Diaghilev". PALABRAS CLAVE: Kirov Ballet, Les Noces, Chopiniana.
Dentro del apartado "Kirov 2003".